The Role of Risk Aversion and Lay Risk in the Probabilistic Externality Assessment for Oil Tanker Routes to Europe - Andrea Bigano; Mariaester Cassinelli; Anil Markandya; Fabio Sferra (Fondazione Eni Enrico Mattei (FEEM), 2006)
Oil spills are a major cause of environmental concern, in particular for Europe. However, the traditional approach to the evaluation of the expected external costs of these accidents fails to take into full account the implications of their probabilistic nature. By adapting a methodology originally developed for nuclear accidents to the case of oil spills, we extend the traditional approach to the assessment of the welfare losses borne by potentially affected individuals for being exposed to the risk of an oil spill. The proposed methodology differs from the traditional approach in three respects: it allows for risk aversion; it adopts an ex-ante rather than an ex-post perspective; it allows for subjective oil spill probabilities (held by the lay public) higher than those assessed by the experts in the field. In order to illustrate quantitatively this methodology, we apply it to the hypothetical (yet realistic) case of an oil spill in the Aegean Sea. We assess the risk premiums that potentially affected individuals would be willing to pay in order to avoid losses to economic activities such as tourism and fisheries, and non-use damages resulting from environmental impacts on the Aegean coasts. In the scenarios analysed, the risk premiums on expected losses for tourism and fisheries turn out to be substantial when measured as a percentage of expected losses; by contrast, they are quite small for the case of damages to the natural environment.
Keywords: Q51; Q53; L91; 330; Oil Spills; Probabilistic Externalities; Risk Aversion; Lay Risk Assessment; Mediterranean